Comparison of the Rate of Complications of Phacoemulsification in Patients with and without Pseudoexfoliation Syndrome (Medical Forum Monthly, 2024)
Objective: The objective of this study was to compare the rate of complications of Phacoemulsification in patients with and without pseudoexfoliation syndrome.Study Design: Cohart study.Place and Duration of Study: This study was conducted at the Department of Ophthalmology, Bahawal Victoria Hospital, Bahawalpur from July 2017 to December 2017.Materials and Methods: This study included 50 eyes of the patient having cataract with pseudoexfolaiton syndrome Group I, and another 50 eyes of patients having cataract without pseudoexfolation syndrome Group II. All the patients underwent phacoemulcification. PMMA IOL 5.5 to 6mm was implanted in all patients after enlarging the incision. Per-operative and postoperative complications were assessed in both the groups and compared.Results: In both the groups no per-operative complications were noted. On 1st postoperative day Group 1, 38 (76%) patients had no complications, 12(24%) developed complications which are striate keratopathy 8 (16%), anterior chamber (AC) reaction 4 (8%).Group II, 1st Postoperative day, 42(84%) patient had no complication, 8(16%) developed complications which are striate keratopathy, 6(12%) developed AC reaction 2(4%). In Group I, on first month 47(94%) had no complication and 3 (6%) developed complication which is AC reaction while in group II, 49(98%) had no complication, 1 (2%) developed complication which is AC reaction. on third month In Group I 47(94%) had no complications and 3(6%) developed complications which are AC reaction 1(2%) and pigment on the IOL surface 2(4%) while in Group II,48(98%) had developed no complications and 2(4%) patients had developed complications which are AC reaction 1(2%) and pigment on the IOL surface1(2%).Conclusion: A planned approach to cataract surgery using the advanced techniques of phacoemulsification, significantly reduces the risk of complications during surgery.Therefore, phacoemulsification is a safe procedure in cataract without pseudoexfoliation syndrome and in selective cases of cataract with pseudoexfoliation syndrome.